Metaphors of economy - Bracker, Nicole; Herbrechter, Stefan (Amsterdam ; New York : Rodopi, 2005)
In recent years the metaphor of economy has proved to have an immense explanatory power in literary and cultural criticism. Everything can be expressed and analysed in terms borrowed from political economy. Language, texts, social structures, and cultural relationships can be construed in the dynamic terms made available by the metaphor of economy, and, more specifically, the economy of the metaphor. The metaphor of economy allows to show the dynamic processes of exchange, circulation and interested negotiation. The essays in this volume display approaches to cultural and discursive practices derived from the methods and texts of economics. They provide a body of literary and cultural criticism founded upon economic paradigms, which makes apparent the genealogy of our economic thought and the suggestion that looking at human exchange can enrich our understanding of culture. The interest of this volume is manifold: it gives a historical account of the development of economics, elucidates the emergence of theories governed by economic metaphors and clarifies the impact of the metaphor on theories of textuality. It also provides an exchange between economists and literary and cultural critics by combining literary and cultural criticism with economics and covers a wide range of topics which are of interest to scholars from various disciplines. This volume provides a critical exchange which hopes to enrich both economics and literature.
Desire as Capital: Getting a Return on the Repressed in Libidinal EconomyPart III: Narrative Economies; Lolita -- A Region in Flames; Dire Straits: Paul Auster's The Music of Chance and the Economic Loss; Revolutionist Consumers: The Application of Sacrifice in Ruskin, Bataille and Henry James; "Money, for the Night is Coming:" Gendered Economies of Aging in the Novels of Jean Rhys and James Joyce; The Quest for Values: Traditional Sources in Two Late Nineteenth-Century Novels of Adventure; Contributors.
Includes bibliographical references.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Economics and literature; Economics in literature; Économie politique et littérature.; Économie politique dans la littérature.; TRAVEL -- Special Interest -- Literary; LITERARY CRITICISM -- General; Economics and literature; Economics in literature; Economie; Cultuursociologie; Literatuurkritiek; Metaforen